Inhibitory Effect on Nitric Oxide Release in LPS-Stimulated Macrophages and Free Radical Scavenging Activity of Croton linearis Jacq. Leaves - Jesús García Díaz; Rosalia González Fernández; Julio César Escalona Arranz; Gabriel Llauradó Maury; Daniel Méndez Rodríguez; Linda De Vooght; Enrique Molina; Emmy Tuenter; Luc Pieters; Paul Cos (MDPI AG, 2022)
Oxidative stress is an important component of many diseases including cancer, along with inflammatory and neurodegenerative processes. Natural antioxidants have emerged as promising substances to protect the human body against reactive oxygen and nitrogen species. The present study evaluates the inhibition of nitric oxide (NO) production in LPS-stimulated RAW 264.7 murine macrophages and the free radical scavenging activity of Croton linearis Jacq. leaves. UPLC-QTOF-MS analysis identified 18 compounds: nine alkaloids with a morphinane, benzylisoquinoline or aporphine nucleus, and nine O-glycosylated-flavonoids with quercetin, kaempferol and isorhamnetin as the aglycones. The crude extract (IC50 21.59 µg/mL) and the n-hexane fraction (IC50 4.88 µg/mL) significantly reduced the NO production in LPS-stimulated macrophages but with relatively high cytotoxicity (CC50 75.30 and CC50 70.12 µg/mL, respectively), while the ethyl acetate fraction also showed good activity (IC50 40.03 µg/mL) without affecting the RAW 264.7 cell viability. On the other hand, the crude extract, as well as the dichloromethane and ethyl acetate fractions, showed better DPPH and ABTS free radical scavenging activities. Considering the chemical composition and the activity observed for Croton linearis leaves, they may be considered a good source of antioxidants to combat oxidative damage-related diseases.